Kedudukan Hukum Surat Pesanan sebagai Perikatan Kontraktual dalam Pengadaan Barang/Jasa Pemerintah: Telaah Yuridis Putusan PN Jakarta Selatan Nomor 272/Pdt.G/2022/PN Jkt.Sel. - Ade Rizki Fauji; Naima Fatia Rahmaniah; Panji Adhiwinata Kusuma (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
This research examines the legal position of purchase orders within Indonesia's system of binding agreement and contract law. Purchase orders constitute important instruments in economic activities that establish legal relationships between parties, particularly in government procurement of goods and services. The research focuses on the legal position of purchase orders from the perspective of binding agreement and contract law, as well as the considerations of the South Jakarta District Court in Decision Number 272/Pdt.G/2022/PN Jkt.Sel. This research employs a normative juridical method with statutory and case approaches, analyzing primary and secondary legal materials. The findings demonstrate that purchase orders hold a strong legal position as contractual agreements when they fulfill the requirements of Article 1320 of the Indonesian Civil Code, which is reinforced by Supreme Court Jurisprudence Number 1506 K/Pdt/2002. The South Jakarta District Court recognized purchase orders as valid grounds for civil claims. Purchase orders have legally binding force and can serve as the basis for civil claims when they reflect a genuine legal relationship between the parties.